The F region and topside ionosphere response to a strong geomagnetic storm at Arecibo. Issue 8 (29th August 2013) - Gong, Yun; Zhou, Qihou; Zhang, Shao Dong; Aponte, Néstor; Sulzer, Michael; González, Sixto A.
Abstract: [1] We analyze the data derived from the Arecibo incoherent scatter radar measurements to investigate the response of the F region and topside ionosphere to a strong geomagnetic storm that occurred during the period of 5–6 August 2011. The meridional wind was extremely enhanced at the early stage of the storm. The peak velocity reached approximately 300 m/s at an altitude of 340 km, which is seldom seen at the Arecibo latitude. During the storm, the vertical ion drift caused by the meridional wind was positively correlated with that caused by the electric field, which is opposite to the quiet time relationship. The disturbed vertical ion drifts resulted in large ionospheric perturbations in the F and topside regions. Several collapses were observed in hm F 2 during the storm night. Nm F 2 rapidly increased after the storm and then decreased around midnight. At an altitude of 610 km, the concentration of H + and O +, and the ratio of H + over electron density all exhibited large variations. The ratio of H + over electron density changed from less than 10% to more than 80% in a matter of 2 hours in the morning of 6 August. One explanation for such a behavior is that vertical transport dominates over charge exchange late at night due to the lower concentration of O + . Key Points: Storm caused traveling atmospheric disturbance Largest meridional wind observed at Arecibo Storm caused large ionosphere compositional changes.